Implementation of Discovery Learning Model to Improve Students' Collaborative Skills in Biology Learning in Secondary Schools - Hajar, Ibnu; Mel, Maizirwan; Ferazona, Sepita; Ferawati, Ferawati; Amelia, Natasya Risky (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
The evolving demands of 21st-century education increasingly emphasize collaborative competencies as core components of global learning goals, including at the senior high school level. In response, this study aims to investigate the implementation of the Discovery Learning model in enhancing the collaborative skills of Grade X.8 students at SMAN 11 Pekanbaru. Employing a descriptive research method, data were collected through structured observations and documentation. The analysis was conducted using descriptive statistical techniques. Findings reveal that the application of Discovery Learning positively influences students’ collaborative abilities, particularly in group discussions, laboratory practicums, and material presentations. The structured stages of Discovery Learning provide opportunities for students to actively engage, communicate, and co-construct knowledge, thereby strengthening their interpersonal and team-working skills. The study concludes that the Discovery Learning model is effective in fostering collaboration among students. It further recommends optimizing the educator’s role as a facilitator and integrating complementary strategies to enhance the efficacy of the model’s implementation in classroom settings.Keywords: collaboration skills, discovery learning, learning models